The girl who fought back : Vladka Meed and the Warsaw Ghetto Uprising - Greene, Joshua, 1950- (Scholastic Focus, 2024)
"Warsaw, Poland, 1940s: The Nazis are on the march, determined to wipe out the Jewish people of Europe. Teenage Vladka and her family are among the thousands of Jews forced to relocate behind the walls of the Warsaw Ghetto, a cramped, oppressive space full of starvation, suffering, and death. When Vladka's family is deported to concentration camps, Vladka joins up with other young people in the ghetto who are part of the Jewish underground: a group determined to fight back against the Nazis, no matter the cost. Vladka's role in the underground? To pass as a non-Jew, sneaking out of the ghetto to blend into Polish society while smuggling secret messages and weapons back over the ghetto wall. Every move she makes comes with the risk of being arrested or killed. But Vladka and her friends know that their missions are worth the danger--they are preparing for an uprising like no other, one that will challenge the Nazi war machine. This astonishing true story of the Warsaw Ghetto Uprising, told through the lens of Holocaust survivor and educator Vladka Meed, introduces readers to a crucial piece of history while highlighting the persistence of bravery in the face of hate."--